Failure investigation and prevention for off-shore pipes with internal pressure - Ng, Peiqi. (2011)
Pipes are classified as one of the safest and convenient mode of transportation for flammable liquid and hazardous gases. Fatigue cracks are commonly identified in the welded region of the pipes, regardless of its application. Even with an insignificant crack, its presence may cause a huge reduction in the capability of the materials during application.